Paleomagnetic studies in Skarðsheiði, South-Western Iceland (Dataset) ... - Kristjánsson, Leó; Guðmundsson, Ágúst (Magnetics Information Consortium (MagIC), 2023)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Paleomagnetic studies in Skarðsheiði, South-Western Iceland ...